The Effectiveness of Science Learning Tools Based on Education Sustainable Development (ESD) to Improve Problem-Solving Skills - Dwita Dana Pradipta; Madlazim; Eko Hariyono (IJORER : International Journal of Recent Educational Research, 2021)
This study aims to determine the effectiveness of practicing problem-solving skills from ESD-based science learning tools. This research is development research with the ADDIE development model and a one-group pre-test post-test design. Data collection methods using validation and tests. Learning tools in all aspects are stated to be very valid so that they can be implemented. The pre-test average score was 52.96 and the post-test score was 79.84 with an N-gain score of 0.67 in the moderate category. This shows that students can be improve in problem-solving skills with ESD-based learning. Students can improved problem-solving skills in the Lapindo mud phenomenon by integrating the liquid pressure material (Archimedes Law and Bernoulli's Law) with the ESD concept (social, ecological, and economic). In terms of ecology, Lapindo mudflow can be overcome by applying Bernoulli's Law. In the economic sector, the overflowing Lapindo mud can be used as a building material. This is studied in the material of Archimedes Law. In the social point, students can communicate the results of problem-solving with the concept of ESD to the surrounding community.